Species evolution: cryptic species and phenotypic noise with a particular focus on fungal systematics - Ekanayaka, Anusha H.; Karunarathna, Samantha C.; Tibpromma, Saowaluck; Dutta, Arun Kumar; Tennakoon, Danushka Sandaruwan; Karunarathna, Anuruddha; Chukeatirote, Ekachai; Dai, Dong-Qin; Stephenson, Steven L.; Maharachchikumbura, Sajeewa S. N.; Liu, Chao; Phillips, Alan J. L. (Frontiers in Cellular and Infection Microbiology, 2025)
The evolution of a species can be understood in the context of two major concepts—the cryptic species concept and the phenotypic noise concept. The former represents morphologically indistinguishable but genetically distinct evolutionary lineages, while the latter represents the phenotypic variations of an isogenic population. Although the concept of cryptic species currently represents a general topic, its effect on other aspects of biology, such as biodiversity, ecology, evolutionary biology, and taxonomy, is still unclear. In particular, cryptic species cause complications and prevent the development of a clear taxonomy. The phenotypic noise concept or phenotypic plasticity generally refers to the various expressions of phenotypes in different environments. Hence, the cryptic species concept refers to genetic variations, while the phenotypic noises concept is about non-genetic variations. Although both concepts are opposites, they each contribute significantly to the evolutionary process of an organism. Despite the extensive research studies and publications discussing those two concepts in separate accounts, a concise account that combines and compares both concepts are generally lacking. Nevertheless, these are essential to understand the evolutionary process clearly. This review addresses the available literature on this topic, intending to provide a general and overall discussion on both the cryptic species concept and the phenotypic noise concept and their effect on evolution, ecology, biodiversity, and taxonomy with a special focus on fungal systematics. hence, several fungal case studies representing the two concepts are presented, compared, and discussed for a better understanding.